Analisis Penerapan Sistem Informasi Akuntansi dan Keuangan Daerah (SIAKD) dalam Peningkatan Kualitas Laporan Keuangan di Kantor Sekretariat Daerah Provinsi Bengkulu - Gustini, Gustini; Azuwandri, Azuwandri; Putra, M Bima Eka; Novrianda , Herry (Jurnal Adminitrasi Bisnis Nusantara, 2024)
The goal of this research is to analyze implementation of Sistem Informasi Akuntansi dan Keuangan Daerah (SIAKD) in increasing quality of financial report in Office of Region Secretariat Province Bengkulu.The method of research is used the research is descriptivly with survey-explanatory approach. The collecting data were done by directly observasion and questionnary. The conclusion of this research are : First, implementation SIAKD at pada Biro Pengelolaan Keuangan Daerah Kantor Sekretariat Daerah Provinsi Bengkulu have suited with the roles in Peraturan Pemerintah Nomor 24 tahun 2005 tentang Standar Akuntansi Pemerintahan. Second, quality financial report before implementate SIAKD have much mistakes are caused by employees’s mistakes (human error). The doing also need much time. The quality of financial report after implementate SIAKD can finish accurately in short time. Third, the advantages of using SIAKD, is it can make financial report quickly and accurately, it also tranparansi and accountable. The minus of using SIAKD, is it can can show financial report such as : Catatan atas Laporan Keuangan, and so it still do manually.